Developing Students' Scientific Literacy Skills in Driving Schools Through the Use of Local Wisdom-Based Physics Lesson E-module - Era Nurkumala Sari; Sarah Miriam; Suyidno Suyidno (Berkala Ilmiah Pendidikan Fisika, 2023)
Scientific literacy is the primary goal of learning physics. However, this ability does not need to be carried out well in schools, especially those integrated with local wisdom. Therefore, this study aims to describe the feasibility of South Borneo’s local wisdom-based physics e-modules on renewable energy materials to improve students' scientific literacy. This study uses the ADDIE development model. However, it is still in the ADD stage: Analyze, Design, and Development. Data were collected using an e-module validation instrument emphasising content and construct validity. The validation results show that three experts said that the physics e-module based on local wisdom on renewable energy materials developed is feasible and can be used as a reference for physical libraries to improve students' scientific literacy.